2016
DOI: 10.2174/1573403x12666160803100928
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Imaging in Heart Failure with Comorbidities

Abstract: Imaging modalities stand at the frontiers for progress in congestive heart failure (CHF) screening, risk stratification and monitoring. Advancements in echocardiography (ECHO) and Magnetic Resonance Imaging (MRI) have allowed for improved tissue characterizations, cardiac motion analysis, and cardiac performance analysis under stress. Common cardiac comorbidities such as hypertension, metabolic syndromes and chronic renal failure contribute to cardiac remodeling, sharing similar pathophysiological mechanisms s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 211 publications
(161 reference statements)
0
6
0
2
Order By: Relevance
“…It has been reported that the current survival rate of CHF with multiple causes is comparable to that of patients with malignant neoplastic diseases, with a high mortality rate exceeding 50% [ 15 ]. However, conventional diagnosis fails to provide a comprehensive analysis of the cardiac function, resulting in a high risk of misdiagnosis and underdiagnosis, along with the invasiveness of many examinations, which prevents desirable diagnostic results [ 16 , 17 ]. Ultrasound technology has been widely used in clinical practice, and cardiac ultrasound provides a comprehensive evaluation of the cardiac function by effectively displaying detailed information such as cardiac data and blood flow data of the examined subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the current survival rate of CHF with multiple causes is comparable to that of patients with malignant neoplastic diseases, with a high mortality rate exceeding 50% [ 15 ]. However, conventional diagnosis fails to provide a comprehensive analysis of the cardiac function, resulting in a high risk of misdiagnosis and underdiagnosis, along with the invasiveness of many examinations, which prevents desirable diagnostic results [ 16 , 17 ]. Ultrasound technology has been widely used in clinical practice, and cardiac ultrasound provides a comprehensive evaluation of the cardiac function by effectively displaying detailed information such as cardiac data and blood flow data of the examined subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the guidelines emphasize that no single modality can answer all pathophysiologic queries in HF. However, due to high availability, low cost and great versatility, ECHO is an indispensable tool in the evaluation of HF [ 50 ]. Furthermore, echocardiography can identify atrial myopathy, which is characterized by alterations of left atrial function/size, has been recognized as a possible mechanism for ischemic stroke independently of the presence of atrial fibrillation.…”
Section: Resultsmentioning
confidence: 99%
“…The time between subsequent pulse sequences delivered to the same slice is known as repetition time (TR). The delay between the delivery of the RF pulse and the reception of the echo signal is known as the time to echo (TE) [16]. Following an intravenous bolus of gadolinium, three time phases are considered (T1, T2, and T2*) to differentiate soft tissues based on their magnetic characteristics, characterized by relaxation times [16].…”
Section: Mechanism Of Mrimentioning
confidence: 99%
“…The delay between the delivery of the RF pulse and the reception of the echo signal is known as the time to echo (TE) [16]. Following an intravenous bolus of gadolinium, three time phases are considered (T1, T2, and T2*) to differentiate soft tissues based on their magnetic characteristics, characterized by relaxation times [16]. The first pass can be utilized for perfusion imaging to detect ischemia, where hypovascular areas will not improve shortly after contrast is administered.…”
Section: Mechanism Of Mrimentioning
confidence: 99%